Fluid escape features as relevant players in the enhancement of seafloor stability?. (1st October 2019) - Riboulot, Vincent; Imbert, Patrice; Cattaneo, Antonio; Voisset, Michel
Abstract: Fluid migration within the sedimentary column contributes significantly to slope failure and pockmark formation and can be an effective triggering mechanism to generate submarine landslides. Pockmarks are thus commonly listed among geohazards. Contrary to these accepted notions, we propose here an alternative view of pockmarks with an example from the Eastern Niger Submarine Delta: Pockmarks and associated chimneys may increase or modify the shear strength of sedimentary layers and locally enhance seafloor stability. The analysis of two 3D seismic volumes shows that a landslide deposit divides into two branches around a cluster of three pockmark chimneys, interpreted to impede its further development. The morphological characteristics of a slide constrained by fluid seepage features show the potential role of fluid escape in marine sediment strengthening.